THE EFFECTS OF FEMINIZATION OF MIGRATION ON FAMILY FUNCTIONS IN TSHOLOTSHO DISTRICT, ZIMBABWE - Thebe, Phillip; Maviza, Gracsious (Advances in Social Sciences Research Journal, 2019)
The paper explores the effects of Feminization of Migration on Family Functions using Tsholotsho District of Zimbabwe as a case in point. It seeks to establish whether there are changes in the manner in which families execute their production, socialization and reproduction functions following the absence of a female member(s) and to understand how these family dynamics resonate with the increase in female migration. The study targeted households with incidents of female migration and employed multistage sampling to choose respondents. Data was gathered using Focus Group Discussions, Questionnaires and Key Informant Interviews. It emerged from the study that due to feminized movements: (i) families have become more of consumption rather than production units; (ii) most families are akin to changing their reproductive systems and; (c) that the very systems that aid socialization in families have been denigrated. These feminized movements have sometimes dwindled families’ abilities of executing their functions and improving their wellbeing. The paper concludes that family functions are neither static nor homogeneous and this partly is due to feminized migration and the life course, which sometimes coerce families to realign their functions so as to deal with various livelihood threats.